The Role of Women's Cooperatives as an Institution to Empower Women in Supporting the Achievement of the SDGs - Gijanto Purbo Suseno; Nataliningsih Nataliningsih (International Journal of Ethno-Sciences and Education Research, 2023)
Sustainable Development Goals (SDGs) are international programs that must be supported by other countries, especially developing countries such as Indonesia. The SDGs contain 18 goals and 169 targets that are expected to be achieved by 2030. There are 4 goals that can be directly implemented by women, namely without poverty, without hunger, a healthy and prosperous life, and gender equality. The purpose of this study is to map the extent of the role of the Women's Cooperative as an institution for empowering women in order to achieve a family without poverty, without hunger, in health and prosperity and gender mainstreaming in supporting the achievement of the SDGs by 2030. Women's cooperative (Women’s Co-op) is a group of women who have the same goal. The study was conducted using a descriptive method, with a literature study approach. The results of the study indicate that the empowerment of women's cooperative members that has been carried out by 5 (five) Women's Co-ops, shows progress in entrepreneurship skills, social progress, increased income and the same opportunity. Therefore, to support the SDGs more quickly, it is necessary to develop a model of coaching and training for members of women's cooperatives as well as a model of fostering secondary women's cooperatives for primary women's cooperatives so that poverty, hunger, welfare and gender mainstreaming are evenly distributed throughout Indonesia.